2015
DOI: 10.1186/s13256-015-0626-4
|View full text |Cite
|
Sign up to set email alerts
|

Testicular metastasis as the first clinical manifestation of pancreatic adenocarcinoma: a case report

Abstract: IntroductionTesticular metastases from pancreatic carcinomas are extremely rare and are usually seen in the late phase of the disease. Fewer than 10 cases have been reported in the literature to date, all of which occurred in patients more than 50 years old. Herein we describe the first case, to our knowledge, of testicular metastasis as the first clinical manifestation of pancreatic carcinoma in a young adult.Case presentationA 36-year-old Caucasian man presented to our institution with an acutely developed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Kiefer[ 3 ] first described epididymal spread originating from primary pancreatic cancer, which was incidentally discovered during autopsy in 1927[ 3 ]. To date, less than 30 cases have been reported including 1from China[ 4 ], 2from South Korea[ 5 , 6 ], 10from Japan[ 7 ], 6from the United States[ 8 - 12 ], and the other 5from European countries[ 13 - 17 ]. Scrotal or inguinal metastases occur worldwide, although Japanese males have a much higher incidence, accounting for half of the published cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kiefer[ 3 ] first described epididymal spread originating from primary pancreatic cancer, which was incidentally discovered during autopsy in 1927[ 3 ]. To date, less than 30 cases have been reported including 1from China[ 4 ], 2from South Korea[ 5 , 6 ], 10from Japan[ 7 ], 6from the United States[ 8 - 12 ], and the other 5from European countries[ 13 - 17 ]. Scrotal or inguinal metastases occur worldwide, although Japanese males have a much higher incidence, accounting for half of the published cases.…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 cases experienced weight loss or other digestive discomfort[ 8 , 14 , 16 ]. One patient was referred due to severe acute pain in the right testis[ 13 ] and may have been diagnosed as orchitis. Kim et al [ 6 ] and colleagues reported a case of metastatic testicular tumor from pancreas, whose only initial symptom was hydrocele[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung metastasis is quite common, while secondary neoplasia of testicular cancers from solid tumors, except for leukemia and lymphoid carcinoma, is extremely rare, accounting for only 0.02% to 3.6% of all testicular neoplastic lesions. 3 Metastatic involvement of the testicle by UTUC is even rarer. Testicular metastasis is generally found occasionally during orchiectomy for prostate cancer or at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Kiefer ED first described metastatic epididymal spread from primary pancreatic carcinoma in 1927 as an incidental autopsy finding [3]. To date, less than 30 cases have been reported, including one from China [4], two from South Korea [5][6], ten from Japan [7], six from the USA [8][9][10][11][12] and the other five from European countries [13][14][15][16][17]. The scrotal or inguinal metastasis propensity occurs world-wide, although there is a remarkably high incidence among Japanese men, who account for one harf of published cases.…”
Section: Discussionmentioning
confidence: 99%